Synthesis, Characterization And Co2 Adsorption Of Caco3, Ca(Oh)2 And Inert Materials Incorporated Ca(Oh)2 - Hlaing, Nwe Ni (2016)
Calcium oxide (CaO) based materials have been proposed as potential candidates for CO2 adsorption to reduce the emission of carbon dioxide (CO2) into the atmosphere especially from the combustion of fossil fuel power plants. In this research, aragonite (CaCO3), calcite (CaCO3), calcium hydroxide (Ca(OH)2) and inert materials incorporated calcium hydroxide (Ca(OH)2) were synthesized by hydrothermal, sol-gel assisted hydrothermal and precipitation methods, respectively. Various parameters such as hydrothermal temperature (8 h - 72 h), addition of polyacrylamide (PAM), sodium hydroxide (NaOH) concentration (2 M - 10 M), cetyltrimethyl ammonium bromide (CTAB) concentration (0.2 M - 0.9 M) and different inert incorporated materials (Mg, Zr, Ce and (Zr-Ce)) on as-synthesized samples were characterized. And then, the CO2 adsorption performances of calcium oxide (CaO) based adsorbents derived from as-synthesized samples were investigated. In the case of hydrothermal method, 1D aragonite (CaCO3) nanorods are observed at 72 h hydrothermal reaction time when PAM is used as an additive, whereas 1D aragonite nanorods are obtained without using PAM at 12 h reaction time. In sol-gel assistance hydrothermal method, 3D calcite (CaCO3) hollow microspheres are attained with 2 M of NaOH concentration, while nanostructured calcium hydroxide (Ca(OH)2) is obtained by precipitation method at high CTAB concentration of 0.9 M. On the other hand, Mg, Zr, Ce and (Zr-Ce) incorporated Ca(OH)2 samples exhibit different surface morphologies. The CO2 adsorption capacities of calcium oxide (CaO) derived from 1D aragonite CaCO3 nanorods, 3D calcite CaCO3 hollow microspheres and nanostructured calcium hydroxide Ca(OH)2 after first cycles are 0.80 g-CO2/g-adsorbent, 0.62 g-CO2/g-adsorbent and 0.71 g-CO2/g-adsorbent, respectively. However, these capacities drop to 0.38 g-CO2/g-adsorbent, 0.39 g-CO2/g-adsorbent and 0.48 g-CO2/g-adsorbent after 10 cycles, respectively. It can be seen that CaO derived from Ca(OH)2 with surface area 64.57 m2/g exhibits the best CO2 adsorption capacity after 10 cycles (0.48 g-CO2/g-adsorbent), but the decay in adsorption capacity with number of cycles is observed. The development of cyclic stability can be observed in CaO-based adsorbents derived from Mg, Zr, Ce and (Zr-Ce) incorporated Ca(OH)2 samples. The CaO-based adsorbent derived from Mg-Ca(OH)2 shows slightly decrease in capacity from 0.67 g-CO2/g-adsorbent after first cycle to 0.57 g-CO2/g-adsorbent after 10 cycles, while CaO-based adsorbents produced from Zr and Ce-incorporated Ca(OH)2 samples exhibit the obvious cyclic stability during 10 cycles, 0.38 g-CO2/g-adsorbent and 0.24 g-CO2/g-adsorbent, respectively. The CaO-based adsorbent derived from (Zr-Ce) acetates incorporated Ca(OH)2 sample increases the capacity from 0.59 g-CO2/g-adsorbent after first cycle to 0.63 g-CO2/g-adsorbent after 10 cycles. The higher adsorption capacity and better cyclic stability during 10 cycles are attributed to the high BET surface area (155.80 m2/g), a wide range of micro/mesopore size distribution (1.7 nm - 30 nm) and the presence of high temperature sintering resistance Ce2Zr3O10 compound.